Design Principles for Shared Digital Twins in Distributed Systems - Hendrik Haße; Hendrik van der Valk; Frederik Möller; Boris Otto (Business & Information Systems Engineering, 2022)
Digital Twins offer considerable potential for cross-company networks. Recent research primarily focuses on using Digital Twins within the limits of a single organization. However, Shared Digital Twins extend application boundaries to cross-company utilization through their ability to act as a hub to share data. This results in the need to consider additional design dimensions which help practitioners design Digital Twins tailored for inter-company use. The article addresses precisely that issue as it investigates how Shared Digital Twins should be designed to achieve business success. For this purpose, the article proposes a set of design principles for Shared Digital Twins stemming from a qualitative interview study with 18 industry experts. The interview study is the primary data source for formulating and evaluating the design principles.
Keywords: 000; Digital Twin; Design principles; Data sharing; Qualitative research